Memprediksi Determinan Kinerja Karyawan Pada Sektor Perbankan BUMN Regional - Waode Atika Sri Amaliah; Salim Basalamah; Sanusi Sanusi (Universitas Nusantara PGRI Kediri, 2023)
The current study aims to investigate the impact of motivation, reward, and work discipline affect the performance of employees in the regional banking sector. Multiple regression analysis based on data from 70 employees of Bank Rakyat Indonesia (BRI) Tbk. Census sampling method was performed to prove the research hypothesis. The results show a positive and significant relationship between rewards, work discipline and employee performance. In contrast, the motivation found did not play a role in improving employee performance. Theoretically, these findings provide an indication of new enrichment regarding the interaction of the synergy of motivation, rewards and work discipline to influence employee performance in an area. Managerially, leaders can develop strategic human resource management plans that are relevant to the company context.